Neutrosophic Multi-Criteria Decision Making - Florentin Smarandache (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Neutrosophic logic and set are gaining significant attention in solving many real-life problems that involve uncertainty, impreciseness, vagueness, incompleteness, inconsistency, and indeterminacy. A number of new neutrosophic theories have been proposed and have been applied in Multi-Criteria Decision-Making, computational intelligence, multiple-attribute decision-making, image processing, medical diagnosis, fault diagnosis, optimization design, and so on. Neutrosophic logic, set, probability, statistics, etc., are, respectively, generalizations of fuzzy and intuitionistic fuzzy logic and set, classical and imprecise probability, classical statistics and so on. This Special Issue gathers 11 original research papers that report on the state of the art and recent advancements in Multi-Criteria Decision-Making using neutrosophic environment in computing, artificial intelligence, big and small data mining, group decision-making problems, pattern recognition, information processing, image processing, and many other practical achievements.